COVID-19 and Neurological Manifestations - Balaini, Neeraj; Modi, Manish (Annals of the National Academy of Medical Sciences (India), 2020)
Coronavirus disease 2019 (COVID-19) is a viral illness caused by severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) which has taken the form of a pandemic. It mainly presents as fever, cough, shortness of breath involving respiratory system but neurological manifestations are increasingly being recognized worldwide and even virus RNA was demonstrated to be present in cerebrospinal fluid of a patient. SARS-CoV-2 involves both central nervous system and peripheral nervous system. Virus can enter the neural tissue from hematological route or through retrograde transport from nerve endings. Physicians especially neurologists should be aware regarding neurological manifestations as patient can present with these conditions in emergency. We therefore reviewed the neurological diseases or complications associated with COIVID-19 in available literature.
Keywords: coronavirus; COVID-19; neurologic complications